2006
DOI: 10.1111/j.1365-2761.2006.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Host preference of adult Caligus elongatus Nordmann in the laboratory and its implications for Atlantic cod aquaculture

Abstract: The sea louse Caligus elongatus utilizes a range of marine fish species as hosts, and it has been suggested that fish farms are infected with adult C. elongatus from wild fish hosts. We assessed experimentally whether dislodged lice return to their original host species. Adult lice from wild lumpfish and saithe were presented to lumpfish, sea trout, Atlantic cod, saithe and European plaice. All fish species became infected. Lumpfish and cod were strongly preferred, followed by saithe, trout and plaice. Lice fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Caligus elongatus adults readily transfer between hosts and species (Øines et al 2006) and have been found on several species which are commercially fished in Faroese waters, including cod (Gadus morhua), haddock (Melanogrammus aeglefinus), saithe (Pollachius virens), mackerel (Scomber scombrus), and herring (Clupea harengus) (Neilson et al 1987, MacKenzie & Morrison 1989, Øines et al 2006, Heuch et al 2007). All of these fish species inhabit the coastal zone to various degrees, and aggregate around fish farms (Dempster et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Caligus elongatus adults readily transfer between hosts and species (Øines et al 2006) and have been found on several species which are commercially fished in Faroese waters, including cod (Gadus morhua), haddock (Melanogrammus aeglefinus), saithe (Pollachius virens), mackerel (Scomber scombrus), and herring (Clupea harengus) (Neilson et al 1987, MacKenzie & Morrison 1989, Øines et al 2006, Heuch et al 2007). All of these fish species inhabit the coastal zone to various degrees, and aggregate around fish farms (Dempster et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Demersal fish such as Atlantic cod have been observed to dislodge parasites (Barber et al, 2000;Øines et al, 2006) by scraping their lateral side along the bottom substrate. Documenting the functional significance of scouring with respect to parasite load is particularly important for cod (and salmon) given their increasing economic value in aquaculture production (Lysne et al, 1994), which can be compromised by external parasite infestations (Øines et al, 2006), and thus monitoring such behaviour becomes diagnostic.…”
Section: Algorithm As Parasite Indicator With Internally Attached Tagsmentioning
confidence: 99%
“…They are usually attached to their hosts, but may also occur in the plankton (Boxshall 1974, Neilson et al 1987. Adult lice readily change hosts (Bruno & Stone 1990, Øines et al 2006. This implies that a fish can be infected independently by both copepodids and adults.…”
Section: Introductionmentioning
confidence: 99%